Pregnancy with COVID-19-related severe ARDS: A case report from rural critical care unit in India (Indian Journal of Case Reports, 2022)
Acute Respiratory Distress Syndrome (ARDS) can frequently occur as a complication of Coronavirus Disease 19 (COVID-19). As a result of the increasing number of COVID-19 cases around the world, it is inevitable that ARDS will complicate some pregnancies with COVID-19. At present, there are scarce data to guide decision-making on the timing of delivery for these patients. We present a case of a pregnant woman at 30 weeks gestation with COVID-19-related ARDS, who was successfully managed with lung protective strategies for mechanical ventilation and early delivery by cesarean section in the rural critical care setting.